2007
DOI: 10.1016/j.ijgo.2006.10.006
|View full text |Cite
|
Sign up to set email alerts
|

The risk of malignancy index in discrimination of adnexal masses

Abstract: The RMI is an appropriate method in diagnosing adnexal masses with high risk of malignancy and forwarding to gynecological oncology centers for suitable surgical operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
3
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 17 publications
(13 reference statements)
4
33
3
1
Order By: Relevance
“…Furthermore, high CA-125 levels are known to be indicative of other gynecological conditions such as endometriosis and pelvic infections. 17,18 As a result, serum CA-125 levels show low sensitivity (42.8%) and accuracy (80.2%) in our study.…”
Section: Discussioncontrasting
confidence: 60%
“…Furthermore, high CA-125 levels are known to be indicative of other gynecological conditions such as endometriosis and pelvic infections. 17,18 As a result, serum CA-125 levels show low sensitivity (42.8%) and accuracy (80.2%) in our study.…”
Section: Discussioncontrasting
confidence: 60%
“…Yamamoto et al [12], who created their own model of a malignancy risk index, added the parameter of tumor size (S) to the RMI, and have termed it RMI 4. Retrospective and prospective validation of the four versions of the RMI have been conducted in different clinical studies [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], where a cutoff value of 200 for RMI 1-3 and 450 for RMI 4 showed the best discrimination between benign and malignant pelvic masses, with high levels of sensitivity and specificity (sensitivity 51%-90%, specificity 51%-97%). The main advantage of four RMIs is that it is a simple scoring system that can be applied directly into clinical practice without the introduction of expensive or complicated methods (such as computed tomography scan, magnetic resonance imaging, and wholebody positron emission tomography).…”
Section: Jung-woo Park Et Al Four Rmis In Pelvic Massesmentioning
confidence: 99%
“…Ulusoy et al 8 reported that an RMI cut off 153, there was increased incidence of malignant tumors detected. In our study the cut off for RMI ONE and TWO was taken as 200.…”
Section: Resultsmentioning
confidence: 99%